2015
DOI: 10.4172/2155-6121.1000213
|View full text |Cite
|
Sign up to set email alerts
|

Readability, Presentation and Quality of Allergy-related Patient Information Leaflets; A Cross Sectional and Longitudinal Study

Abstract: Objective:Patient information leaflets (PILs) are widely used to reinforce or illustrate health information and to complement verbal consultation. The objectives of the study were to assess the readability and presentation of PILs published by Allergy UK, and to conduct a longitudinal assessment to evaluate the impact of leaflet amendment and revision on readability.Methods:Readability of Allergy UK leaflets available in 2013 was assessed using Simple Measure of Gobbledegook (SMOG) and Flesch-Kincaid Reading G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“… 2 Two studies conducted in the UK found that the mean readability of medications in the UK market was above the reading level of the general population. 1 , 4 The existing literature has assessed the readability of medications and found gaps between the readability score and target patients' readability level. Patient information leaflets have readability levels that are higher than recommended to be understood by the general population, which is a concerning issue in communicating medication information to patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 Two studies conducted in the UK found that the mean readability of medications in the UK market was above the reading level of the general population. 1 , 4 The existing literature has assessed the readability of medications and found gaps between the readability score and target patients' readability level. Patient information leaflets have readability levels that are higher than recommended to be understood by the general population, which is a concerning issue in communicating medication information to patients.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 31 , 32 A limited number of small-scale studies with methodological variations were conducted to investigate the readability level of leaflets of different medications. 1 , 2 , 4 The existing studies found gaps between the readability of PILs and grade level for readability by the average adults, which need to be addressed to avoid the impact of misinterpretation of medication instructions on patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation